Internal Versus Institutional Barriers to Gender Equality: Evidence from British Politics - Noor Kumar; Uyseok Lee; Matt Lowe; Olaitan Ogunnote (CESifo GmbH, 2024)
Weekly lotteries determine which politicians ask the UK Prime Minister a question in front of a male-dominated, packed, and noisy chamber. Women are 12% less likely to submit questions than same-cohort men, and this gap does not close with lottery-induced experience asking a question, or with years of service. However, the gender gap almost fully closes after a switch to a format in which questions are asked to a smaller, quieter, audience. The switch differentially draws in women with quieter voices. Our findings support institutional change, rather than adaptation through experience, as a response to gender gaps in adversarial settings.
Keywords: J16; D91; D72; 330; gender gap; public speaking; gender norms; politician behaviour